Estratégias de melhoria da renda da agricultura familiar: análise a partir da base social da CRESOL/Prudentópolis - Ternoski, Simão (2013)
The emergence of a market economy, has made the social context of agriculture were changed, especially in its forms of organization of work and production. Submission productive market economy determine the diversification strategies of livelihoods in agriculture, family and require efforts to expand the capabilities in pursuit of greater potentiality of living. The market causes deprivation of opportunities that may exacerbate or assist rural poverty situations thus ask: diversification strategies adopted by rural households can reduce vulnerabilities and increase income? From this problem, the following possible answers were sought: (1) Farmers with more concentrated income have lower total income,(2) Farmers pluriativas have higher income farmers monoativas; (3) Farmer with better access to resources livelihoods has higher income. Therefore, the objective of this research is to identify strategies to improve rural income among the cooperative's Rural Credit Cooperative Interaction with Solidarity - CRESOL / Prudentópolis - PR. As a result, it was found that: (1) diversification of livelihoods allows institutions of higher income levels, advancing pluriactivity becomes positive in order to raise revenue, (2) the index of income diversification is not associated with higher levels of income, (3) and expanding access to resources for livelihoods, considered among the human, social, environmental, physical and financial, (exogenous variables), it follows that not all explain the same proportion of total income (endogenous variable), but explained that the capital income of explanation presented parameters considered highly significant.